Prilaku Kuat Tekan Beton Porous Menggunakan Air Laut - Adnan Adnan; Muh. Alim (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Porous concrete has high porosity so that water can pass through the cavities in the concrete. The application of porous concrete is usually for parking areas, pedestrian sidewalks, road shoulders, drainage, roads with low traffic volume. Indonesia is an archipelagic country, most of Indonesia's territory is by the sea so it is very possible to use sea water as a substitute for fresh water for porous concrete. This research aims to determine the comparison of compressive strength of porous concrete mixed with sea water and normal porous concrete with variations in the water cement (fas) factor. In this study, a concrete mixture with a water cement (fas) factor of 0.30 and 0.35 was used. The test object used was a 15x30 cm cylindrical concrete test object for the compressive strength test. The test on porous concrete was carried out during the curing period of 28 days. The test results for the compressive strength of normal porous concrete with a water cement (fas) factor of 0.30 and 0.35 are 6.658 Mpa and 4.435 Mpa, then for porous concrete mixed with sea water with a water cement (fas) factor of 0.30 and 0, 35, namely 6,700 Mpa and 3,374 Mpa. The test results show that the sea water mixture in porous concrete does not affect the compressive strength of porous concrete, whereas the use of variations in the water cement factor (fas) shows that the compressive strength of porous concrete, both normal porous concrete and porous concrete mixed with sea water, has decreased. as the value of the water cement (fas) factor used increases.